Análisis a las Competencias que Inciden en la Inserción Laboral de los Egresados de la Carrera de Licenciado en Educación en un Colegio al Norte del País. - Jaime Bautista, Karla Alejandra; Cárdenas González, Víctor Manuel; Madrigal Lozano, María Magdalena (Revista Daena: International Journal of Good Conscience)
Currently, the work environment has presented us with new challenges, often in parallel with the development of innovations in the modern world, the objective is to create multicultural organizational environments, improvement strategies, comprehensive and innovative solutions for the requirements of companies designed by graduates of university education. Therefore, university education for graduates must provide a set of skills appropriate to labor, social, and economic needs so that they can successfully integrate into the present and future global reality. The graduate is expected to continually develop in the various contexts necessary for his or her professional development. It is crucial that university education equips graduates with a set of skills that adjust to labor, social and economic needs, facilitating their successful integration into the present and future global reality. It is expected that the graduate can continually evolve in various contexts necessary for their professional development. The purpose of this study is to identify the relationship that university competencies such as self-learning, Information Technologies, Communication, Knowledge and Digital Learning (ICTCAD), languages, analytical understanding and problem solving have in the job placement of college graduates of education of the UANL. Results of our phenomenology were obtained through a sociodemographic study and statistical results from a multiple linear regression analysis using the statistical techniques and instruments of the SPSS and SMART PLS statistical packages.